The Future of Clothing and Textiles in Kenyan Secondary Schools - Serem, Dorcas J; Mukwa, C; Kafu, PA (Nurture, 2010)
The aim of this study was to investigate the attitude of Home Science students and teachers towards Clothing and Textiles in Home Science discipline of the secondary school curriculum. Home Science is one of the technical and vocational subjects introduced to Africans in Kenya towards the end of the 19th century by Christian missionaries (Wandera, 1967). Home Science was fragmented into Needlework and Foods and Nutrition until 1985 when it was consolidated. The objectives were to establish the teachers’ and students’ attitude towards instruction of Clothing and Textiles and determine problems affecting the instruction of Clothing and Textiles. Simple and systematic random sampling techniques were used to choose schools offering Home Science and students to participate in the study respectively. Data was collected using questionnaire from 409 students and 27 teachers from 21 secondary schools offering Home Science in three (3) districts in Western Kenya. Descriptive statistics was used in data analysis and relationship between variables was established using chi-square tests. The study established that 61% and 78% of teachers and students respectively have positive attitude towards Clothing and Textiles.